Inactivation of MS-2 virus in water by rotational generator of hydraulic shock - Benjamin Bizjan; Gašper Rak; Sabina Kolbl Repinc; Polonca Ropret; Janez Kosel (Heliyon)
This study investigates the effect of hydraulic shock waves on inactivation of MS-2 bacteriophage, a norovirus surrogate. A falling circular jet of water spiked with the MS-2 (∼1000 PFU/mL) was repeatedly impacted by a rotating blade, resulting in occurrence of hydraulic shock waves within the liquid region adjacent to the impact. The proof-of-concept rotational generator of hydraulic shock treating 9 L of water spiked with viruses was able to achieve 3 logs reduction of viral plaque count within 80–100 liquid passes at moderate blade impact velocities (namely, 70 and 88 m/s) despite the water temperature not exceeding 40 °C and no detectible cavitation. Within the first 20 liquid passes, most MS-2 capsid proteins were degraded, with their concentration reduced from 22 μg/mL to only 7.3 μg/mL. Due to the lack of further capsid protein destruction, additional reduction in MS-2 plaque count in subsequent 80 passes is indicative of damage inflicted to the viral recognition receptors. All this suggests that shockwaves of moderate amplitude (few tens of MPa) alone are sufficient for effective viral inactivation. Considering this and the device's good scalability potential, rotational hydraulic shock generators could prove effective in treating virus-contaminated waters.